Occurrence of thiamethoxam in coffee (Coffea arabica L.) leaves and fruits following a soil drench application of the insecticide - Zimermann Vilela Torres, Fabrícia; de Oliveira Rigitano, Renê Luís; Castro Torres, Lucas (Coffee Science - ISSN 1984-3909, 1970)
The occurrence of thiamethoxam in coffee leaves and fruits after a soil drench application of the insecticide was assessed. The experiment was carried out in a five-year-old coffee plantation, in which 0.6 g of Actara 250 WG® was applied per plant. Samples of fruits and leaves were collected 30, 60 and 90 days after application and their thiamethoxam content was assessed. Thiamethoxam residues in the grains and hulls of fruits collected 120 days following the application were also determined, after drying and processing of the fruits. Thiamethoxam contents in the samples were determined by high performance liquid chromatography. A bioassay was done in the laboratory to assess the efficiency of thiamethoxam in the control of the coffee berry borer (Hypothenemus hampei (Ferrari)) by feeding adult females treated or untreated fruits. The results showed that concentrations of the insecticide in the leaves and fruits were highest 30 days after application. The occurrence of thiamethoxam in the fruits provided a partial control of the coffee berry borer.